2021
DOI: 10.3390/ph15010006
|View full text |Cite
|
Sign up to set email alerts
|

Co-Delivery of Letrozole and Cyclophosphamide via Folic Acid-Decorated Nanoniosomes for Breast Cancer Therapy: Synergic Effect, Augmentation of Cytotoxicity, and Apoptosis Gene Expression

Abstract: Breast cancer is one of the most prevalent causes of cancer mortality in women. In order to increase patient prognosis and survival rates, new technologies are urgently required to deliver therapeutics in a more effective and efficient manner. Niosome nanoparticles have been recently employed as therapeutic platforms capable of loading and carrying drugs within their core for both mono and combination therapy. Here, niosome-based nanoscale carriers were investigated as a targeted delivery system for breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 51 publications
(59 reference statements)
1
30
0
Order By: Relevance
“…After a 24 h incubation period, suspensions of various samples (0–35 µg/mL) were added to the medium and incubated for another 24 h period as well as for 48 and 72 h. In the next step, the contents of the 96-well plates were replaced by the MTT solution in each well after another 4 h of incubation at 37 °C in a 5% CO 2 environment. To dissolve the purple formazan crystals, the medium was replaced and added to each well with 0.05 mL of dimethyl sulfoxide (DMSO) [ 39 , 40 ]. Finally, the absorbance of each well was measured using a microplate reader at 570 nm.…”
Section: Methodsmentioning
confidence: 99%
“…After a 24 h incubation period, suspensions of various samples (0–35 µg/mL) were added to the medium and incubated for another 24 h period as well as for 48 and 72 h. In the next step, the contents of the 96-well plates were replaced by the MTT solution in each well after another 4 h of incubation at 37 °C in a 5% CO 2 environment. To dissolve the purple formazan crystals, the medium was replaced and added to each well with 0.05 mL of dimethyl sulfoxide (DMSO) [ 39 , 40 ]. Finally, the absorbance of each well was measured using a microplate reader at 570 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Cur has the capacity to induce apoptosis in cancer cells and reduces metastasis via EMT inhibition. Furthermore, Cur supplementation promotes sensitivity to cancer chemotherapy [ 9 ]. However, the health benefits of Cur are limited due to poor bioavailability, so that upon oral administration, a low amount of this valuable compound is absorbed by the intestine and excretion occurs for the rest.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, niosomes can increase the residence time of various drugs in the stratum corneum and epidermis, while minimizing their systemic absorption [ 16 ]. Several studies have reported the encapsulation of different drugs into niosomes, such as topotecan [ 14 ], letrozole [ 17 ], curcumin [ 18 ], and melittin [ 19 ], aiming to improve their hydrophilicity, bioavailability, and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%